1990
DOI: 10.5014/ajot.44.3.249
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Therapy for Children With Perinatal HIV Infection

Abstract: This article discusses occupational therapy for children with perinatal HIV infection and their care-givers. An interdisciplinary early intervention and preschool program serving these children is described. Current medical and neurological research is reviewed to serve as a basis for occupational therapy intervention. Therapeutic approaches that integrate physical, neurological, developmental, and psychosocial needs are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

1992
1992
2001
2001

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The child with AIDS may feel ashamed, fearful, or angry at being an innocent victim. With unstable family structures and frequent hospitalizations, the child may become increasingly isolated and thus deprived of the physical and emotional comfort necessary for development (Anderson et al, 1990). Therefore, emotional and social support services are needed to prevent further isolation, depression, and other related consequences of AIDS.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The child with AIDS may feel ashamed, fearful, or angry at being an innocent victim. With unstable family structures and frequent hospitalizations, the child may become increasingly isolated and thus deprived of the physical and emotional comfort necessary for development (Anderson et al, 1990). Therefore, emotional and social support services are needed to prevent further isolation, depression, and other related consequences of AIDS.…”
mentioning
confidence: 99%
“…The diagnostic category of pediatric AIDS was developed in 1986, when medical professionals and researchers confirmed that children could contract HIV and at least 240 cases were reported to the Centers for Disease Control (CDC; Anderson, Hinojosa, Bedell, & Kaplan, 1990). Within 1 year, from 1987-1988, the incidence of AIDS in children rose from 1% to 2% of all AIDS cases and is expected to double each year.…”
mentioning
confidence: 99%
“…The Center for Disease Control and Prevention (CDC, 1986) classified the HIV/AIDS progression into four stages: Stage 1 (body's initial short-lived flu-like response to AIDS virus); Stage 2 (HIV continues to replicate in the body and affect the immune system); Stage 3 (HIV has caused enough damage to the immune system to cause signs and symptoms); Stage 4 (fullblown AIDS; the immune system is severely damaged and compromised). Throughout all the stages, persons with HIV/AIDS require services in several or all of the performance areas (Anderson et al, 1990;Chan et al, 1996;Fish & Rudman, 1998;Gutterman, 1990;Molineux, 1997;Pizzi, 1990a;Pizzi, 1990b;Pizzi, 1996;Weinstein, 1990;Williams, 1990). Denton (1987) delineated five functions for occupational therapy practitioners who provide services to PWAs: (a) education of occupational therapy personnel about HIV/AIDS, (b) observation of precautions, (c) evaluation, (d) treatment, and (e) consultation with other health team, family and support members.…”
mentioning
confidence: 99%
“…To date, the occupational therapy intervention-oriented literature related to PWAs has addressed the progression of HIV/AIDS (Pizzi, 1990b;Schindler, 1988;Weinstein, 1990;Weinstein & DeNeffe, 1990), issues PWAs face throughout the progression of the disease (Palinicek, 1998;Schindler, 1988;Snyder, 1993;Weinstein, 1990), and described evaluation and intervention strategies (Anderson et al, 1990;Denton, 1987;Fish & Rudman, 1998;Gutterman, 1990;Molineux, 1997;Pizzi, 1990a;Pizzi, 1996). However, the literature has not included descriptions of occupational therapy referral patterns for PWAs and subsequent intervention frequency patterns or priorities, for each of the four CDC stages of the disease.…”
mentioning
confidence: 99%